Successful Management of a Typical Class 3 Invasive Cervical Root Resorption with Modified Pulpotomy: A Case Report - Asgary , Saeed; Roghanizadeh , Leyla (Iranian Endodontic Journal, 2024)
Invasive cervical root resorption (ICRR) is a rare and clinically complex condition marked by the progressive loss of dental hard tissues below the junctional epithelium. This case report outlines the management of a 32-year-old female patient presenting with ICRR class 3 affecting a maxillary incisor. Despite the absence of symptoms, the expansive nature of the defect warranted conservative surgical intervention. The procedure involved the surgical removal of inflamed tissues, followed by an ultraconservative modified pulpotomy utilizing calcium-enriched mixture (CEM) cement through a surgical window. The selected intervention is substantiated by its potential benefits, such as minimal removal of tooth structure and the inherent biocompatibility and sealing capabilities of CEM cement. A one-year follow-up revealed arrested resorption, re-establishment of periodontal attachment, and successful esthetic restoration, affirming the efficacy of vital pulp therapy in surgically addressing advanced ICRR. Accurate diagnosis, strategic treatment planning, and a patient-centered approach proved critical in achieving favorable outcomes.